Extractive Separation of Al(III) and Ni(II) by Di-2-Ethylhexyl Phosphoric Acid -Kerosene System from Aqueous Fluoride Medium: Extractive Separation of Al(III) and Ni(II) (Biological Sciences - PJSIR, 2009)
In the study of the extractive separation of Al(III) and Ni(II) by di-2-ethylhexyl phosphoric acid D2EHPA- kerosene from aqueous fluoride medium, about 94% Al(III) and 2% Ni(II) were extracted with 0.3 M D2EHPA (pH 2.1 and temperature 30±1 °C). Extraction of Ni(II) decreased with increasing extractant concentration. D2EHPA-kerosene- fluoride system showed better extraction of Al(III) with higher extractant concentration and aqueous pH and vice versa for the extraction of Ni(II). The maximum separation factor (b~1380) was obtained for Al(III) at 20 °C and decreased to (b~732) at 60 °C. The separation of Al(III) from Ni(II) was favoured at normal temperature. Extraction followed the order Al(III) >>>Ni(II). About 99% stripping of Al(III) was attained from the loaded 0.20 M D2EHPA. Much faster extraction of Al(III) compared to Ni(II) and preferential loading were shown by D2EHPA-kerosene in the presence of fluoride ion in the aqueous phase. Separation of Al(III) was the most outstanding from Ni-Al-F-complex solution.